Phytochemical screening and evaluation of antifertility activity of Streblus asper leaf extract in female albino mice - Kakali Deka,, Tapashi Sutradhar, Barsha Sarma, Anjumani Ojah, Sonot Deori, Mridul Kumar Borthakur (Journal of Applied Pharmaceutical Science, 2025)
The plant kingdom offers a wealth of biologically active substances with diverse pharmacological effects. India has a long-standing tradition of using medicinal plants for their contraceptive properties, both for females and males. In this study, mice were administered methanolic leaf extract of Streblus asper (MESA) at 200 and 400 mg/kg body weight doses alongside 17β estradiol (1 μg/kg body weight) as a standard drug. Also, phytochemical analysis of the leaves was done by using methanol, ethanol, water, and petroleum ether as a solvent. Phytochemical analysis revealed that methanolic extract possesses the highest phytoconstituent and percentage yield, while petroleum ether extract possesses the lowest. Based on that, methanol extract was used for further investigation in this study. The findings revealed that MESA altered the duration of various phases of the estrous cycle of mice. Furthermore, the extract also exhibited dose-dependent anti-implantation and abortifacient effects. This study represents an initial step in verifying the plant’s purported antifertility properties.
Keywords: Anti-implantation, abortifacient, estrous cycle, Streblus asper